Percutaneous versus open pedicle screw fixation for treatment of type A thoracolumbar fractures - Kocis, Jan; Kelbl, Martin; Kocis, Tomas; Návrat, Tomas (European journal of trauma and emergency surgery, 2020)
BACKGROUND: The purpose of this study was to evaluate the effectiveness between percutaneous and open pedicle screw fixation without fusion for treating type A3 and A4 thoracolumbar fractures. Traumatic thoracolumbar burst fracture is a common pathology without a consensus on the best treatment approach. Percutaneous pedicle screw fixation (PPSF) systems have been recently introduced in the treatment of spinal fractures to reduce the adverse effects associated with the conventional open approaches, such as iatrogenic muscle denervation and pain. METHODS: A prospective analysis was made to evaluate consecutive 46 patients with type A3 and A4 thoracolumbar fractures. Patients were divided into a percutaneous pedicle screw fixation group (PPSF) and an open pedicle screw fixation group (OPSF). The mean age of patients in PPSF group (12 men, 11 woman) was 49.9 years and in OPSF group (10 men, 13 women) 52.2 years. For the purpose of evaluation, the radiological assessment of the bisegmental Cobb angle, the loss of correction, the volume of blood loss, operation time, cumulative radiation time and dose were recorded and compared. RESULTS: All patients were followed up for 12 months. There were no significant differences between OPSF and PPSF in the Cobb angle preoperative and postoperative angle and the loss of bisegmental correction. In PPSF group, the mean preoperative Cobb angle was 10.9° and improved by 4.5° postoperatively, and in OPSF group the preoperative angle was 12.1° and postoperatively improved by 3.8°. Significant differences between OPSF and PPSF were found in the mean cumulative radiation time, radiation dose and operation time. PPSF group also had a significantly lower perioperative blood loss. CONCLUSIONS: Both open and percutaneous short-segment pedicle fixation were safe and effective methods to treat thoracolumbar burst fractures. Percutaneous fixation without fusion seems to be suitable for type A3 and A4 fractures.
Keywords: Fracture Fixation, Internal; délka operace; Percutaneous; Trauma; Humans; lidé středního věku; Lumbar Vertebrae; kohortové studie; Spinal Fractures; Female; Aged; mladý dospělý; dospělí; výsledek terapie; Pedicle Screws; senioři; lidé; fraktury páteře; krvácení při operaci; miniinvazivní chirurgické výkony; pedikulární šrouby; Cohort Studies; Thoracolumbar; vnitřní fixace fraktury; bederní obratle; Adult; Spine; Operative Time; ženské pohlaví; Male; Middle Aged; dávka záření; Treatment Outcome; Young Adult; Radiation Dosage; hrudní obratle; mužské pohlaví; prospektivní studie; Thoracic Vertebrae; Blood Loss, Surgical; Minimally Invasive Surgical Procedures; Prospective Studies